2022
DOI: 10.1007/s12672-022-00593-z
|View full text |Cite
|
Sign up to set email alerts
|

Local control comparison of early-stage non-melanoma skin Cancer (NMSC) treated by superficial radiotherapy (SRT) and external beam radiotherapy (XRT) with and without dermal image guidance: a meta-analysis

Abstract: Background Various treatments exist for non-melanoma skin cancer (NMSC), but the mainstay is surgical removal. Superficial radiotherapy (SRT) is one non-surgical technique that has been used for over a century but fell out of favor due to the advent of Mohs micrographic surgery (MMS). A new technology that combines a 22 megahertz (MHz) dermal ultrasound with SRT (US-SRT) enables tumor visualization before, during, and after treatment, and demonstrates increased cure rates and reduced recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…The 2-year and 5-year absolute LC observed in this study are identical, which is consistent with the generally accepted premise that most failures in NMSC occurs within 2–3 years (Yu et al 2022 ; Samarasinghe and Madan 2012 ). There is low likelihood of local recurrence for early-stage NMSC after 2 years (Amin et al 2017 ; Samarasinghe and Madan 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 2-year and 5-year absolute LC observed in this study are identical, which is consistent with the generally accepted premise that most failures in NMSC occurs within 2–3 years (Yu et al 2022 ; Samarasinghe and Madan 2012 ). There is low likelihood of local recurrence for early-stage NMSC after 2 years (Amin et al 2017 ; Samarasinghe and Madan 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…A high-resolution ultrasound (HRUS) simulation was performed to establish the field and determine the lesion for proper selection prior to treatment. This visualization is necessary to determine tumor breadth and depth for width, energy and dose selection (Yu et al 2022 ). Thereafter, HRUS was performed during each treatment and after completion in order to make real-time modifications and assess for treatment response, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all lesions had minimal or mild toxicity scores (RTOG 0, 1, 2). Our updated results support that IGSRT, with longer follow-up, continue to offer a high local control rate felt to be comparable to the best surgical techniques (14) (15) and continues to be an effective noninvasive, non-surgical treatment modality for NMSC with its major advantages of avoiding the pitfalls of surgery clinically, cosmetically, physiologically and psychologically. These updated results validate our prior statement that IGSRT should be a primary non-surgical option presented to patients for treatment of their early-stage NMSC lesions.…”
Section: Discussionsupporting
confidence: 60%
“…Two recent studies, a metanalysis and a logistic regression analysis, compared IGSRT studies to large well run SRT/XRT studies without image guidance. Both analyses found that the LC rates for the IGSRT studies were statistically superior to the non-image-guided SRT/XRT studies (14), (15). The image-guided component of SRT utilizes a 22 megahertz (MHz) dermal ultrasound with color doppler to visualize the superficial depth of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision is the first therapy against NMSC; however, some alternative approaches can be used, i.e. photodynamic therapy, cryotherapy, topical imiquimod 5%, and topical diclofenac sodium 3% [ 8 , 22 , 23 ]. SCCs also arises from squamous cells that line in the mucosal surfaces of the head and neck (HNSCC) including oral cavity, pharynx, larynx, tongue as well an in lung [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%